Main-oval Auroral Emission from a T6 Brown Dwarf: Observations, Modeling, and Astrometry - J. C. Guirado; J. B. Climent; J. D. Bergasa; M. A. Pérez-Torres; J. M. Marcaide; L. Peña-Moñino (The Astrophysical Journal)
From a series of 5 GHz Very Long Baseline Array (VLBA) radio observations taken over a 1 yr span, we present the detection of compact, highly polarized radio emission from the T6 brown dwarf WISE J112254.72+255022.2, compatible with electron cyclotron maser emission. Both the total and polarized lightcurves show variability in correspondence with a rotation period of 1.95 ± 0.03 hr. Comparison with models indicates that the quasi-steady radio emission of this brown dwarf is produced in circumpolar auroral rings, with remarkable similarity to the main-oval auroras in Jupiter. We have detected a large 100% polarized flare in one of the VLBA epochs (2022.82), which may imply the existence of active longitudes in the auroral rings with a nonaxisymmetric beaming cone radiation pattern, similar to the dusk/dawn asymmetries seen in the Jovian radio emissions. We also present a high-precision astrometric analysis of the sky motion of WISE J112254.72+255022.2, resulting in revised values of proper motion and parallax with an improvement in precision of 1 order of magnitude. The common kinematics of WISE J112254.72+255022.2 with its wide companion, the M dwarf LHS 302, is confirmed with submilliarcsecond precision, suggesting that this brown dwarf may have formed by gravitational fragmentation of the outer part of a protostellar disk around LHS 302. The astrometric analysis imposes very tight bounds on the presence of low-mass companions around WISE J112254.72+255022.2, ruling out objects more massive than Saturn. Our results strengthen the analogy between radio-emitting brown dwarfs and the magnetized planets of our solar system.